2011
DOI: 10.1186/1753-4631-5-1
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Decomposition Analysis of the digital arterial pulse during hemorrhage simulation

Abstract: BackgroundMarkers of temporal changes in central blood volume are required to non-invasively detect hemorrhage and the onset of hemorrhagic shock. Recent work suggests that pulse pressure may be such a marker. A new approach to tracking blood pressure, and pulse pressure specifically is presented that is based on a new form of pulse pressure wave analysis called Pulse Decomposition Analysis (PDA). The premise of the PDA model is that the peripheral arterial pressure pulse is a superposition of five individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
2
13

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(107 citation statements)
references
References 25 publications
3
85
2
13
Order By: Relevance
“…The second pulse is thought of being a reflection at the junction between the thoracic and abdominal aorta, as there is a significant decrease in the artery diameter. Similarly, the change in diameter at the juncture between the abdominal aorta and the iliac arteries is regarded to be responsible for the third pulse wave [1] In order to find the unknown model parameters we needed to solve the following optimization problem:…”
Section: Pulse Waveform Analysis By Decomposition Into Basis Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second pulse is thought of being a reflection at the junction between the thoracic and abdominal aorta, as there is a significant decrease in the artery diameter. Similarly, the change in diameter at the juncture between the abdominal aorta and the iliac arteries is regarded to be responsible for the third pulse wave [1] In order to find the unknown model parameters we needed to solve the following optimization problem:…”
Section: Pulse Waveform Analysis By Decomposition Into Basis Functionsmentioning
confidence: 99%
“…For the extraction of physiologically relevant information from single volume pulse cycles, the pulse decomposition analysis (PDA) has proven to be a powerful tool [1]. In the PDA, a single volume cycle is modelled as a linear superposition of basis functions.…”
Section: Introductionmentioning
confidence: 99%
“…First, several reports have shown the utility of HRV is the assessment of short and long term outcomes that reflect physiologic, pharmacologic, and pathologic conditions [8][9][10]. We and others have identified that meditation increases LF and that this has been interpreted as reflecting an increase in the balance of the autonomic nervous system [5,11].…”
Section: Resultsmentioning
confidence: 99%
“…Using a smoother to eliminate false peaks, heart beats can be detected as peaks above a certain threshold. Subsequently, the series of inter beat intervals for a subject are taken to be the differences between times of these peaks and the instantaneous heart rates at each beat are calculated as the inverse of these interbeat intervals [9,10]. For each heart beat, the systolic blood pressure and diastolic blood pressure are taken to be the differences in the pressure components of the raw expression data.…”
Section: Methodsmentioning
confidence: 99%
“…Actually, the parameters of the decomposed Gaussian functions can be deduced from the feature points of the pulse wave such as the crests, troughs, and periods of the pulse wave [5,[20][21][22]. Therefore, it could be better if a user can simply and freely set several feature points through an independent embedded system and let this portable system generate the simulated pulse wave that can meet the user's requirement and approximate the realistic pulse wave with high accuracy [23].…”
Section: Introductionmentioning
confidence: 99%